The comparative study between digital art and conventional art / Mohd Hisham Johari - Johari, Mohd Hisham (2009)
There is no specific term on how to define art. Now days there are two ways and method in producing an artwork. The traditional ways that use apurely tool like brush, scalpel, canvas, oil paint, acrylics, water color, crayon sand surely it use bare hand in making an artwork. The other one is digital art. In digital art, the artworks are being produced using a gadget like drawing tablet, digital camera and a printer. Both ways can be applied in any field of art. Illustration, image and video editing, and other art branches. This study will search on the differences and similarity between these two ways of art. Digital art and traditional art. The study will also explain what is digital art and traditional art. The researcher will unfold what makes an artwork is categories into these two ways of producing an artwork. Hence, this research covers the feedback from the art practitioners. In addition, other feedback also was gained from the questionnaire which involved the respondents who all of them are the students of the Art & Design Faculty in UiTM. Based on the results, a conclusion has been made whether it has complying with the researcher's hypothesis of 'digital art and traditional art can be use together in producing a beautiful artwork' such as drawing, painting, editing or illustration', or not.